0452 Lemborexant Treatment of Older Adults with Insomnia and Objective Short Sleep: Rates of Response and Remission. (25th May 2022) - Edinger, Jack; Krystal, Andrew; Kumar, Dinesh; Pappadopulos, Elizabeth; Lundwall, Christie; Moline, Margaret
Abstract: Introduction: In Phase 3 Study 304 (NCT02783729), lemborexant (LEM) provided significant benefit versus placebo (PBO) on polysomnographic (PSG) endpoints and sleep diary-based sleep onset and maintenance outcomes over 1mo in subjects with insomnia disorder. The study also included the Insomnia Severity Index (ISI) to ensure sufficient insomnia severity at baseline (ISI total score ≥13) and for use as an outcome measure. Subjects met criteria for insomnia disorder and were confirmed to spend between 7-9 hours in bed. Subjects had insomnia with objective short sleep (ISS; [total sleep time; TST] <6hrs) or objective long sleep (TST ≥6hrs). Since patients with ISS may respond less well to therapeutic approaches such as cognitive behavioral therapy for insomnia (CBT-I), we examined rates of response and remission with LEM as defined by the ISI in the ISS subgroup. Methods: Study 304 was a 1mo, randomized, double-blind, PBO- and active-controlled, parallel-group study in female (age ≥55y) and male (age ≥65y) subjects (n=1006). Subjects received PBO, LEM 5mg (LEM5), LEM 10mg (LEM10), or zolpidem tartrate extended-release 6.25 mg (not reported). Baseline PSGs were obtained during a single-blind PBO run-in, followed by paired PSGs on Nights 1/2 and Nights 29/30. The ISI was given at baseline and end of treatment. For these post-hoc analyses, responders were defined as subjects whose decrease from baseline on the ISI was ≥7pts, while remitters achieved ISI total scores <8pts. LEM5 and LEM10 vs PBO differences were evaluated using chi-square tests. Results: 525/743 (70.66%) of subjects in the PBO/LEM groups were in the ISS subgroup. For LEM5, 99/176 (56.25%) were responders and 49/176 (27.84%) were remitters. For LEM10, 97/180 (53.89%) were responders and 50/180 (27.78%) were remitters. For the PBO group, 59/140 (42.14%) were responders and 21/140 (15.00%) were remitters. The responder and remitter rates for LEM5 and LEM10 were statistically significantly greater than those for PBO (all P<0.05). Conclusion: Older adults with ISS achieved clinically meaningful improvement with LEM as assessed at the end of one month of treatment, with nearly 30% considered remitters and >50% considered treatment responders. LEM is a potential therapy for ISS patients who may have limited response to CBT-I. Support (If Any): Eisai Inc.